2022
DOI: 10.1136/bmjopen-2021-050720
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and mental well-being of Black students at UK universities: a review and thematic synthesis

Abstract: BackgroundThere is a knowledge gap about the experiences that affect the mental health of Black university students in the UK. Current research is focused on understanding the continuation, attainment and progression gap between Black students and non-Black students. It is essential to know more about the interactions between personal and institutional factors on the mental health of Black students to explain the inequalities in their experiences and outcomes across the university lifecycle. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…40 Further, racism has been associated with common mental health difficulties in ethnic minority groups in the UK. 38,39,41 Our findings also reveal that financial problems have a considerable influence on the mental health of South Asian people in the UK. 42 Although the impact of economic difficulty on mental health has been acknowledged nationally, ethnic minorities seem to be more disadvantaged because of uncertain residency status or language barriers.…”
Section: Discussionsupporting
confidence: 57%
“…40 Further, racism has been associated with common mental health difficulties in ethnic minority groups in the UK. 38,39,41 Our findings also reveal that financial problems have a considerable influence on the mental health of South Asian people in the UK. 42 Although the impact of economic difficulty on mental health has been acknowledged nationally, ethnic minorities seem to be more disadvantaged because of uncertain residency status or language barriers.…”
Section: Discussionsupporting
confidence: 57%
“…Trammel et al also found in their study among American undergraduates that Latinax and Asian students experienced higher COVID-19 related threat and negative beliefs than White students [ 52 ]. It is to be noted that ethnic minority students have been experiencing disproportionate mental health problems even before the pandemic due to inequality in access, gaps in academic attainment, unequal representation etc., and there is a strong likelihood that these factors may have exacerbated during the pandemic [ 53 ]. Universities should be more vigilant in identifying these at-risk groups and become proactive in dealing with instances of discrimination and, racially motivated hate crimes both inside and outside the campus.…”
Section: Discussionmentioning
confidence: 99%
“…The context of British student support services is therefore interesting. As we have underlined elsewhere, research on the relationships between the British university environment, racial microaggressions, REM student mental health, and the counselling interaction is an underdeveloped yet growing field; Stoll et al ( 2022 ) identify a corpus of twelve articles addressing mental health and mental well-being experiences among Black students at UK universities published between 2010 and 2020. Clearly, this literature emerges from a different cultural context from the USA, which is structured by the legacy of plantation slavery and Jim Crow; nonetheless, work by Arday ( 2018 ), Akel ( 2019 ), Bunce et al ( 2019 ) and others identify the commonplace nature of racial abuse, both overt and implicit, experienced by racialized minority students within the inequitable environments of British universities.…”
Section: Towards Culturally Appropriate Support In Uk Universitiesmentioning
confidence: 99%
“…Clearly, this literature emerges from a different cultural context from the USA, which is structured by the legacy of plantation slavery and Jim Crow; nonetheless, work by Arday ( 2018 ), Akel ( 2019 ), Bunce et al ( 2019 ) and others identify the commonplace nature of racial abuse, both overt and implicit, experienced by racialized minority students within the inequitable environments of British universities. Synthesizing, Stoll et al identify an experience common to Black students of being subjected to racism and racial stereotyping in the classroom, through teaching materials and staff-student and student-student interactions; and for Black women, in addition, being subjected to the overpolicing of their academic knowledge by teaching staff (Stoll et al, 2022 , p. 6). Five of their corpus of twelve studies discussed how “institutional racism, discrimination and hegemonic white privilege made universities toxic spaces for Black students, which affected their mental health and well-being” (Stoll et al, 2022 , p. 7).…”
Section: Towards Culturally Appropriate Support In Uk Universitiesmentioning
confidence: 99%
See 1 more Smart Citation